Differently PEGylated Polymer Nanoparticles for Pancreatic Cancer Delivery: Using a Novel Near-Infrared Emissive and Biodegradable Polymer as the Fluorescence Tracer - Cai, Huazhong; Chen, Yanxia; Xu, Liusheng; Zou, Yingping; Zhou, Xiaoliang; Liang, Guoxin; Wang, Dongqing; Tao, Zhimin (Frontiers in Bioengineering and Biotechnology, 2021)
In this study, a chemically synthetic polymer, benzo[1,2-b:4,5-b′]difuran(BDF)-based donor–acceptor copolymer PBDFDTBO, was individually coated by amphiphilic poly(ethylene oxide)-block-poly(ε-caprolactone) (PEO-PCL) and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-methoxy(polyethylene glycol) (DSPE-PEG or PEG-DSPE), to form stably fluorescent nanoparticles in the near-infrared (NIR) window. The physicochemical properties of the synthesized nanoparticles were characterized and compared, including their size, surface charge, and morphology. In addition, in vitro studies were also performed using two pancreatic cancer cell lines, assessing the cell viability of the PBDFDTBO-included PEGylated nanoparticles formulations. Moreover, in vivo studies were also conducted, using subcutaneous murine cancer models to investigate the polymeric nanoparticles’ circulation time, tumor accumulation, and preferred organ biodistribution. The overall results demonstrated that even with the same PEGylated surface, the hydrophobic composition anchored on the encapsulated PBDFDTBO core strongly affected the biodistribution and tumor accumulation of the nanoparticles, to a degree possibly determined by the hydrophobic interactions between the hydrophobic segment of amphiphilic polymers (DSPE or PCL moiety) and the enwrapped PBDFDTBO. Both PEGylated nanoparticles were compared to obtain an optimized coating strategy for a desired biological feature in pancreatic cancer delivery.